The Link Between Obesity and the Skin - Darlenski, Razvigor; Mihaylova, Vesselina; Handjieva-Darlenska, Teodora (Frontiers in Nutrition, 2022)
Obesity as a multi-organ disease affects the entire human organism, and the skin is no exclusion from this postulate. Skin changes in obese patients have been widely studied with the ones related to mechanical frictions, skin infections, and being skin hypertrophic conditions such as acanthosis nigricans and fibromas (skin tags) being the most common. Almost 60 to 70% of obese patients present with a variety of skin changes. Herein we discuss our own experience and review the complex skin changes in obesity. The role of metabolic syndrome and obesity in particular have recently been involved in the pathogenesis and are responsible for the epidemiological prevalence of chronic inflammatory skin diseases such as psoriasis and atopic dermatitis, as well as skin malignancies. We comment on the role of nutritional interventions in these patients. It has been proven that low-calorie diet and weight loss is related to improvement of inflammatory skin diseases. The readership of this paper will receive up-to-date overview on the connection between obesity and the skin that is of a practical importance to any clinician working in the field